KONTRIBUSI PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN KEPRIBADIAN SISWA DI SMK AZ-ZUBAER LARANGAN TOKOL PAMEKASAN - Evi Febriani, Abdul Munib (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2019)
National development in the field of education is an effort to educate the life of the nation and develop Indonesian people as a whole, namely people who have faith and are devoted to God Almighty and virtuous character, have knowledge and skills, physical and spiritual health, a steady and independent personality, and a sense of responsibility social and national responsibility based on the Pancasila and the 1945 Constitution. The purpose of PAI in schools / madrasah is in an effort to form morals and morality and to awaken religious attitudes of students. The community assesses the role and function of Islamic religious education in schools is seen as not contributing towards it, even further cornering that Islamic religious education is seen as not succeeding in achieving the expected goals of Islamic religious education, as evidenced by the many cases of delinquency in various forms of children. As a result, the role and effectiveness of Islamic religious education in schools is questioned, with an understanding that if Islamic religious education in schools is carried out properly, then people's lives will be better.